Hormonal dynamics during salt stress responses of salt-sensitive Arabidopsis thaliana and salt-tolerant Thellungiella salsuginea - Prerostova, Sylva; Dobrev, Petre I; Gaudinova, Alena; Hosek, Petr; Soudek, Petr; Knirsch, Vojtech; Vankova, Radomira (Plant science, 2017)
Salt stress responses in salt-sensitive Arabidopsis thaliana (2-150mM NaCl) and the closely related salt-tolerant Thellungiella salsuginea (Eutrema halophila, 150-350mM NaCl) were compared to identify hormonal and transcriptomic changes associated with enhanced stress tolerance. Phytohormone levels, expression of selected genes, membrane stability, and Na+ and K+ concentrations were measured in shoot apices, leaves, and roots. Thellungiella exhibited higher salt stress tolerance associated with elevated basal levels of abscisic acid and jasmonic acid, and lower levels of active cytokinins (excluding cis-zeatin) in shoot apices. Analysis of the dynamics of the early salt stress response (15min to 24h) revealed that the halophyte response was faster and stronger. Very mild stress, in our hydropony arrangement 2-25mM NaCl, affected the transcription of genes involved in cytokinin metabolism (AtIPTs, AtCKXs). Mild stress induced in Arabidopsis (50mM) stress responses only in shoot apices, while in Thellungiella (150mM) across the whole plant. Arabidopsis exhibited in hydropony evidence of severe stress above 75mM NaCl and died in 150mM, whereas the halophyte only became severely stressed above 225mM. The responses of individual phytohormones (cytokinins, auxin, abscisic acid, jasmonic acid, salicylic acid and their metabolites) to salinity are discussed.
Keywords: Plant Shoots; Salt-Tolerant Plants; listy rostlin; Potassium; halotolerantní rostliny; Phytohormone; draslík; Arabidopsis; Salt Tolerance; výhonky rostlin; Plant Roots; Cytokinin; regulátory růstu rostlin; sodík; Brassicaceae; Salinity; Salt stress; Stress, Physiological; kořeny rostlin; salinita; Sodium; tolerance k soli; Abscisic acid; Plant Growth Regulators; Plant Leaves; Auxin; fyziologický stres; Halophyte